Diurnal variations of greenhouse gases emissions from reclamation mariculture ponds. (31st May 2020) - Hu, Beibei; Xu, Xiaofang; Zhang, Junfeng (Jim); Wang, Tianli; Meng, Weiqing; Wang, Dongqi
Abstract: Dissolved concentrations, saturation status, and emission fluxes of greenhouse gases (GHGs) in two reclamation mariculture ponds in the Bohai Gulf, China, were measured using the static headspace gas chromatography method and computed using a two-layer model of diffusive gas exchange. The study was conducted during August 2016 to assess diurnal variations in GHGs emissions. The main influencing factors of GHGs emissions from the ponds under the disturbance of artificial management were identified using Spearman correlation analyses and multiple stepwise regression analyses. Results showed that dissolved GHGs concentrations were stable throughout the day, whereas GHGs emission fluxes showed a clear diurnal variation with larger daytime values. The diurnal variation of N2 O emission fluxes was greater than that of CO2 and that of CH4 . Results also showed that pH of pond water was negatively correlated with CO2 and N2 O emission fluxes and that air temperature was positively correlated with CH4 and N2 O emission fluxes. In addition, ammonia (NH4 + -N) was positively correlated with CH4 emission fluxes; water temperature and salinity were positively correlated with N2 O emission fluxes. The estimated annual emissions from the reclamation aquaculture in Tianjin and the Bohai Rim region were 2.53 × 10 5  kg C–CO2, 6.94 × 10 3  kg C–CH4 and 1.11 × 10 3  kg N–N2 O, and 3.42 × 10 7  kg C–CO2, 9.36 × 10 5  kg C–CH4 and 1.50 × 10 5  kg N–N2 O respectively, indicating the important contribution of this fishery sector to GHGs emissions. Highlights: The greenhouse gases (GHGs) emission fluxes from reclamation mariculture ponds showed a clear diurnal variation. Artificial management was an important factor influencing GHGs emissions from reclamation mariculture ponds. Reclamation mariculture ponds were GHGs emission hotpots.